2002
DOI: 10.1148/radiol.2232010810
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low-Contrast Objects: Experimental Comparison of Single– and Multi–Detector Row CT with a Phantom

Abstract: Multi-detector CT is less effective than single-detector CT in detection of small low-contrast objects if sections thinner than 5 mm are used. Results for single- and multi-detector CT were similar for sections 5 mm or thicker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 10 publications
3
32
1
Order By: Relevance
“…The methodology described in our (21,(26)(27)(28)(29)(30)(31)(32)(33)(34)). An important factor that motivates CD analysis is the inclusion of the human observer as part of the imaging chain, which is a critical consideration in all medical imaging systems (35).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology described in our (21,(26)(27)(28)(29)(30)(31)(32)(33)(34)). An important factor that motivates CD analysis is the inclusion of the human observer as part of the imaging chain, which is a critical consideration in all medical imaging systems (35).…”
Section: Discussionmentioning
confidence: 99%
“…The CTDIw applied was adapted to the recommended dose for abdominal CT by the European Guidelines, which suggest CTDIvol values ranging from 17.5 to 29.5 mGy for liver screening investigation [17][18][19][20][21]. In addition, in a previous experimental study performed with a phantom simulating the X-ray absorption of a standard abdomen, it has been demonstrated that for the detection of 5 mm lesions to achieve a CNR of 1, which ensures a detection rate of 100%, the X-ray dose required correspond to a CTDIw=20 mGy [11]. Thus, we determined the acquisition parameters (tube current setting) in order to obtain a CTDIw=23 mGy for all the protocols tested.…”
Section: Discussionmentioning
confidence: 99%
“…A CNR of 1 was necessary to achieve a 100% detection rate of 5 mm lesions, and a CNR of 0.6 to achieve a 100% detection rate of 9 mm lesions. [11]. The lower efficiency of thinner sections in detecting small hepatic lesions may be attributed to the geometric efficiency of the detectors that deteriorates with thin collimation [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations